A numerical investigation of the impact of shield machine’s operation parameters on the settlements above twin stacked tunnels - A case study of Ho Chi Minh urban railway Line 1 - Do Ngoc, Anh; Dias, Daniel; Trong Dang, Thang (Vietnam Journal of Earth Sciences, 2021)
Three-dimensional ﬁnite difference calculations are proposed to investigate the influence of operation parameters of the shield machines during twin stacked tunnel excavation on the surface settlements. The numerical model is validated by experimental data obtained from Hochiminh’s metro line 1 project, used as a reference case in this study. The parametric study focuses on the influence of the face support pressure, the grouting pressure, and the shield’s length. The numerical results indicated that a decrease does not always follow an increase in surface settlements' face and grouting pressure. A shorter shield machine causes smaller surface settlements to develop over single lower and twin stacked tunnels.